Gerakan sarapan sehat anak sekolah (sarasehan) untuk peningkatan pengetahuan ibu tentang sarapan sehat anak sekolah - Fatmah Fatmah (Jurnal Gizi Klinik Indonesia, 2015)
Background:  Breakfast can meet energy requirement of school children to conduct their daily activity all day. But, in reality, there are many school children who do not behave in a healthy breakfast that can meet the needs of 30% of energy. One of reason is a lack of knowledge and practice of the mother in preparing a healthy breakfast for their children.Objective: To assess the influence of media outreach breakfast (booklets, flipchart, and short films) on the mothers' knowledge of healthy breakfast schoolchildren.Method: Design of quasi-experimental one group pre-post test used in the study towards 186 mothers from ten the selected elementary school at Depok City. Mother's knowledge was measured through a questionnaire pre-post test.Results: There was increased in knowledge of mothers at the end of the study with correct answers given by the mother on the question of the type of food that should be avoided at breakfast. Increased knowledge of the mother before and after the study was differed significantly according to age groups (p <0.05). Older age of mother has better knowledge than younger.Conclusion: Knowledge of mothers on healthy breakfast can be improved through counseling using flipcharts, booklets, and short film.